Absolute efficiency of a two-stage microchannel plate for electrons in the 30–900 eV energy range. (10th December 2021) - Apponi, A; Pandolfi, F; Rago, I; Cavoto, G; Mariani, C; Ruocco, A
Abstract: We report on an apparatus able to measure the absolute detection efficiency of a detector for electrons in the 30–900 eV range. In particular, we discuss the characterisation of a two-stage chevron microchannel plate (MCP). The measurements have been performed in the LASEC laboratory at Roma Tre University, whit a custom-made electron gun. The very good stability of the beam current in the fA range, together with the picoammeter nominal resolution of 0.01 fA, allowed the measurement of the MCP absolute efficiency ε . We found an ϵ = ( 0.489 ± 0.003 ) with no evident energy dependence. We fully characterised the MCP pulse shape distribution, which is quasi-Gaussian with a well visible peak above the noise level. We measured a 68 % variation of the average pulse height between 30 and 500 eV. Furthermore, with a deeper analysis of the pulse shape, and in particular of the correlation between pulse height, area and width, we found a method to discriminate single- and multi- electron events occurring within a 10 ns time window.